MXene-assisted organic electrochemical transistor biosensor with multiple spiral interdigitated electrodes for sensitive quantification of fPSA/tPSA - Yi-Cheng Zhu (BMC, 2021)
Abstract Background The ratio of fPSA/tPSA in the "grey zone" of tPSA with the concentration range between 4 ng/ml and 10 ng/ml is significant for diagnosis of prostate cancer, and highly efficiency quantification of the ratio of fPSA/tPSA remain elusive mainly because of their extremely low concentration in patients' peripheral blood with high biosample complexity. Methods We presented an interdigitated spiral-based MXene-assisted organic electrochemical transistors (isMOECTs) biosensor for highly sensitive determination of fPSA/tPSA. The combination of MXene and the interdigitated multiple spiral architecture synergistically assisted the amplification of amperometric signal of biosensor with dual functionalizations of anti-tPSA and anti-fPSA. Results The ultrasensitivity of the biosensor was enhanced by tunable multiple spiral architecture and MXene nanomaterials; and the sensor exhibited improved detection limit of tPSA and fPSA down to 0.01 pg/ml and acceptable performance of selectivity, repeatability and stability. Moreover, the isMOECTs displayed area under the curve (AUC) value of 0.8138, confirming the potential applications of isMOECTs in clinics. Conclusions The merits of isMOECTs biosensor demonstrated the reliability of MXene-assisted organic electrochemical transistor biosensor with multiple interdigitated spiral for ultrasensitive quantification of fPSA/tPSA, suggesting potential current and future point-of-care testing applications. Graphical Abstract